Circulation hot water system with clean filtering capability - LIU LINSONG (2018)
The utility model discloses a circulation hot water system with clean filtering capability, including cold water valve, filtering sterilizing ware, holding water box, circulating pump, recycle valve,clean valve, support frame, scavenge pipe, cylinder, solar panel and hot water valve, be provided with washing tank, activity groove and water catch bowl on the support frame, the activity groove parallel arrangement be in the side of washing tank, the water catch bowl is fixed the bottom of washing tank and respectively with the backward flow mouth intercommunication of washing tank and filteringsterilizing ware, solar panel fixes on the support frame and lie in in the washing tank, the cylinder is fixed on the support frame and lie in in the washing tank. The utility model discloses utilizeholding water box, circulating pump, recycle valve and solar panel to realize that the circulation heating of water heaies up, it is movable from top to bottom that the cylinder pulls the scavenge pipe, realizes the cleanness